1975
DOI: 10.1002/1097-0142(197506)35:6<1597::aid-cncr2820350618>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative irradiation for carcinoma of the rectum and rectosigmoid colon: Report of a national veterans administration randomized study

Abstract: In 1964 the Veterans Administration Surgical Adjuvant Group (VASAG) initiated a large-scale, controlled, randomized protocol to study the role of low-dose preoperative irradiation (2000-2500 rads/10fractions/12 days) in patients with operable adenocarcinoma of the sigmoid colon and rectum. This report analyzes the data in 700 patients, all at 5-year risk. There appears to be a definate benefit to irradiated patients who undergo abdominoperineal resections, when compared with the controls. This advantage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(42 citation statements)
references
References 37 publications
1
39
0
2
Order By: Relevance
“…7,10 -18 The role of preoperative radiotherapy in survival remains controversial, with some studies reporting a minimal effect, 17,19,20 whereas in other trials a significant impact has been shown. [7][8][9]13,14,16,[21][22][23] In a recent meta-analysis, it was suggested that preoperative radiotherapy significantly improves overall and cancer specific survival but much more in patients with Dukes Stage B and C tumors than in patients with Dukes Stage A tumors. 24 However, to our knowledge, the histopathologic characteristics of the response of rectal carcinoma to ionizing irradiation have been poorly documented, and the results reported from different studies often are contradictory.…”
mentioning
confidence: 99%
“…7,10 -18 The role of preoperative radiotherapy in survival remains controversial, with some studies reporting a minimal effect, 17,19,20 whereas in other trials a significant impact has been shown. [7][8][9]13,14,16,[21][22][23] In a recent meta-analysis, it was suggested that preoperative radiotherapy significantly improves overall and cancer specific survival but much more in patients with Dukes Stage B and C tumors than in patients with Dukes Stage A tumors. 24 However, to our knowledge, the histopathologic characteristics of the response of rectal carcinoma to ionizing irradiation have been poorly documented, and the results reported from different studies often are contradictory.…”
mentioning
confidence: 99%
“…Preoperative irradiation for cancer of the lower rectum has been the object of controversies, specially when survival is discussed [2,5,8,9,11,13,[15][16][17][18]20,21,[24][25][26][27][30][31][32][33][34][36][37][38][39] and only a very few randomized statistic papers are able to demonstrate better long-term results [28,35]. Recurrence, especially local recurrence, is responsible for the great majority of deaths in the first two years after surgery [1,7,19].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, however, some authors have demonstrated that the association of neo-adjuvant therapy (radiotherapy or radio-chemotherapy) to surgery can improve the interval-free of cancer and alter the long-term survival rate [7,13,[24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Three separate studies have shown an improvement in 5-year survival rates in the irradiated compared with the unirradiated group. This difference becomes more impressive as the preoperative dose of radiation is increased from 500 rad (Rider 1975) through 2000 rad (Roswit et al 1975) to 5000 rad (Stevens et al 1978). …”
mentioning
confidence: 99%